Oliguria during Hydrocortisone Dosage Wean in Very Low Birth Weight Infants - Sauberan, J. B.; Reed, E. M.; Vaucher, Y. V.; Katheria, A. C. (American Journal of Perinatology, 2014)
Background Intravenous hydrocortisone (HC) is often used in very low birth weight infants (VLBW) but can be complicated by oliguria when discontinued or tapered.Objectives To determine which factors were associated with oliguria during HC taper.Methods We reviewed all VLBW infants who received initial doses of HC ≥ 1 mg/kg/d. The initial dose and duration of HC, and the incidence of oliguria (urine output [UO] < 2 mL/kg/h) during HC taper, were recorded. In those with oliguria, we recorded the change in UO (mL/kg/h), blood pressure, and creatinine.Results The mean initial HC dose was 2.8 ± 1 mg/kg/d, and the mean total duration of HC therapy was 23 ± 25 days. Oliguria occurred in 24% (13/54) of treated infants. These infants were exposed to higher and longer duration of the initial HC dose than infants without oliguria. Oliguria was predicted by the initial HC dose (odds ratio [OR] 5.8, 95% confidence interval [CI] 1.3–25.8, p = 0.02) and by the number of days at initial dose (OR 1.7, 95%CI 1.1–2.7, p = 0.03).Conclusions Oliguria during HC dosage weaning was associated with higher initial HC exposure.
Keywords: hydrocortisone; hypotension; neonate; renal failure; renal dysfunction; oliguria; steroids; very low birth weight infants